Variability of the hepatic α-amilase activities in the liver of fish species from the Sevastopol bays, Black Sea - Kuzminova, Natalya (Biological Communications, 2020)
This paper presents the results of a study of α-amylase activity in liver of widely represented species of twelve Black sea fish. Comparative analysis of interspecies differences showed that the medium level of enzyme activity is very high only in liver of annular seabream and horse mackerel. The Black Sea predators (scorpion fish, stargazer, shore rockling, whiting) have low values of the medium level of enzyme activity (range from 0,02 to 62,79 mg / s / g of protein). Enzyme activity did not depend on fish sex, their age and location. Research has established lack of any link between activity of enzyme and age for both the scorpion fish and high body pickarel. While studying the effects of seasonal features on enzyme activity in the liver of two dominant species in the coastal zone, it was concluded that enzyme activity is lower in winter than in other seasons.